Rompendo o silêncio: uma análise sobre as histórias de meninas com vivências de abuso sexual atendidas pelo CREAS do município de João Pessoa - Andrade, Adathiane Farias de (2011)
The present study entitled "Breaking the Silence: an analysis of some stories of girls who experienced sexual abuse, assisted by CREAS in the city of João Pessoa" focus on the investigation of sexual abuse stories experienced by 8 to 18 year-old girls, either in the intra or extra-familial, and the revelation of the covenant of silence evidenced in such situations of violence, which remains through veiled threats, slowly progressive seduction and communication. It was based on an analytical and methodological story of life, and guided by the qualitative approach, from the stories of sexual abuse of girls, subjected to research, memories, experiences, feelings, silence and unspoken. Throughout this paper we analyzed the ways of violence directed at children and adolescents, whose focus is on sexual violence, specifically abuse, bringing a cutout on the relationship of gender, due to the greater number of cases involving females. Just as the origins of legitimation, reproduction and representations of the society about violence against the juvenile segment, visualizing the progress and setbacks in the field of the rights of this population. The analysis goes through on how the policy is being implemented and operated full protection programs, projects and services that assist children and adolescents in situations of sexual violence. The questions that shed light on research raised about the approach: scenarios of violence, the artifices of seduction from perpetrators; feeling girls in relation to the aggressor, the necessary support for the development occurs, the search for the service, and the signs towards overcoming.